Early Childhood Mobile Puzzle Game for Learning Hijaiyah Letters (Universitas Ahmad Dahlan, 2022)
The use of Arabic in Muslim worship activities is the main and dominant thing to do, especially in the activities of praying and reading the Qur'an. The Arabic language in these two activities is presented in Hijaiyah letters, so that the ability to read Hijaiyah letters is very obligatory and necessary for Muslims from an early age, through learning and playing activities. Salman Al Farisi I Kindergarten in the Yogyakarta area, Indonesia, has taught its students to learn to read Hijaiyah letters. One of the learning activities to recognize Hijaiyah letters is a puzzle game. This study aims to develop a multimedia application for learning Hijaiyah letters. The application was developed according to the needs of early childhood with the concept of a learning environment and playing through smartphone devices. User-Centered Design (UCD) was used in this study which consisted of six steps: Identifying Needs, Determining Context of Use, Determining Needs, Generating Solution Design, Design Evaluation, and Implementation. This research produces applications that suit system requirements and user needs with good multimedia quality. The results of testing the quality of multimedia show that the application gets a score of 4.53 out of a scale of 5. This score shows that the application has a very good rating.